Analisis Kinerja Pegawai dalam Memberikan Pelayanan Administrasi di Kecamatan Majalaya Kabupaten Karawang - Oktia Dita Suciati; Rahmat Hidayat; Ani Nurdiani Azizah (Peneliti.net, 2022)
The purpose of this study is to analyze how the performance of employees in providing administrative services at the Majalaya District office, Karawang Regency and it is hoped that the results of this study can be a suggestion for Majalaya District, Karawang Regency in an effort to improve the performance of quality, responsive sub-district employees, and meet the needs and aspirations public. The research method in this study uses a descriptive method with a qualitative research approach, namely a study that aims to provide an overview of how the performance of sub-district employees in administrative services in Majalaya District is. The results of research from field observations show that administrative services related to employee performance in serving the community are good but need to carry out operational procedures optimally. The effectiveness of the performance at the Majalaya District Office is said to have not been maximized. In the process of administrative services carried out by the Public Service section itself, in reality it has not been maximized, this can be seen from the service process that is not completed on time. Then, the use of resources as a support in achieving goals is less than optimal.